Strengthening the Value of Independent Characters Through Blended Learning Models During the Covid 19 Period: Penguatan Nilai Karakter Mandiri Melalui Pembelajaran Model Blended Learning di Masa Covid 19 - Anisa Widhi Oktavian; Akhtim Wahyuni (Academia Open, 2022)
This qualitative descriptive study conducted at Mi Ma'arif Kedungsolo aimed to explore the strengthening of independent character values through blended learning models during the Covid-19 period. The research subjects included principals, teachers, students, and parents. Data was collected from July to December 2021 using observation, interviews, and documentation techniques, with data validity checked through technical triangulation. The findings revealed that learning was conducted through a blended approach, with students divided into two groups: those studying at home and those attending classes. Various online platforms such as WhatsApp, YouTube, and Instagram Live were utilized to facilitate learning. The instilling of independent character values was emphasized by teachers through assigning schoolwork that required independent problem-solving and direct interaction with teachers. However, the study identified obstacles to the implementation of blended learning, including limited material explanation and an overreliance on assigning tasks solely via WhatsApp. The implications of this study underscore the importance of addressing these challenges to foster effective blended learning environments that promote independent character development among students. Highlights: Blended learning during Covid-19: Examining the implementation of blended learning models to adapt to the challenges posed by the Covid-19 pandemic, ensuring continuity of education and fostering independent character values. Strengthening independent character values: Investigating how teachers emphasize independence in student assignments and the role of blended learning in cultivating independent character values among students at Mi Ma'arif Kedungsolo. Challenges and obstacles: Identifying the obstacles faced in implementing blended learning, including limited material explanation and an overreliance on communication solely through WhatsApp, and exploring strategies to overcome these challenges for effective blended learning experiences. Keywords: Blended learning, Independent character values, Covid-19, Qualitative descriptive study, Mi Ma'arif Kedungsolo.